Farlige barn? - Hilde Dahl (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Homicides are rare in Norway, and minors committing homicide are even rarer. While such offenses require a response, they also require considerations regarding the effect a prison sentence would have on the young offender. In some cases, the considerations are challenged by a perceived need to protect society from future acts of violence and harm. Thus, some of these minors are not only penalized for what they have done, but also labelled a danger. A question of relevance is how this dangerousness is assessed. This paper aims to provide historical insight into a complete selection of homicide cases from Norway in the period 1955-1982, where the offenders were allminors, many were imprisoned, and some also deemed dangerous. These cases represent society’s view on children’s capacity for harm over a long period.